The relationship of sex and sexual orientation to self-esteem, body shape satisfaction, and eating disorder symptomatology - Yean, Chetra; Benau, Erik; Dakanalis, Antonios; Hormes, Julia M.; Perone, Julie; Timko, Alix (Frontiers in Psychology, 2013)
There is increasing interest in understanding what role, if any, sex and sexual orientation play in body dissatisfaction, its correlates to distress, and its relationship to disordered eating. The goals of the present study were to examine: (a) differences in sex and sexual orientation in internalization of societal pressure to modify physical appearance, components of body image dissatisfaction, self-esteem, and eating disorder symptomatology and (b) whether the internalization-eating disorder symptomatology was mediated by the different components of body image dissatisfaction and low self-esteem. The present data support several key trends in the literature: men generally reported less body dissatisfaction, internalization of socio-cultural standards of beauty, drive for thinness, and disordered eating, but a greater drive for muscularity than women; results also indicated that different components of body image dissatisfaction and low self-esteem partially mediated the relationship between internalization and eating disorder symptomatology. Gay men reported significantly more body dissatisfaction, internalization, eating disorder symptomatology, drive for thinness, and drive for muscularity than heterosexual men. Compared to heterosexual women, lesbians reported increased drive for muscularity, lower self-esteem, and lower internalization; however, they did not significantly differ on body dissatisfaction, drive for thinness or disordered eating. Correlation coefficients between body shape dissatisfaction and several aspects of mental distress were significantly larger for gay men than heterosexual men; the same coefficients did not differ between lesbian women and heterosexual women. Results of path analyses indicated that the relationship between internalization and disordered eating differs for gay and heterosexual men but not for lesbian and heterosexual women. These results call attention to lesbians as a generally understudied population.